Distribution of Bacillus thuringiensis Berliner isolated from rhizosphere in Syria among different crops. (Damascus University Journal of agriculture sciences, 2021)
A total of 117 samples were collected  during 2010 / 2011 from the rhizosphere of 24 different plant species in several Syrian provinces. A round 345 bacterial isolates were identified as Bacillus sp. using the thermal shock method, and a number of 122 isolates were found to belong to Bacillus thuringiensis (Bt) according to different biochemical tests, sodium acetate (0.25 M), morphology of bacterial colonies, and microscopic examination. Results indicated the widespread distribution of the genus Bacillus in all Syrian provinces. The percentage of Bt isolated from rhizosphere was 35.36%, most of them were isolated from Daraa (48 isolates), and from Hama (38 isolates), less number in Aleppo and Idlib. As for the distribution of Bt in different plants, results revealed 36 isolates (29.5%) from lentils, and 31 isolates (25.4%) from wheat, and the lowest ratio was 0.81% from tomatoes, alfalfa and walnuts. On the other hand, the study failed to isolate this bacteria from beans in Idlib, Homs, Quneitra, and from wheat in Aleppo and Tartous.
Keywords: : Bacillus thuringiensis, rhizosphere, Syria.